Factors Influencing the Process of Translating - Wong, Dongfeng; Shen, Dan (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractTranslation is a complex process, involving linguistic, cultural and personal factors. This article seeks to show how these factors constitute the main source of translation difficulties. The authors suggest that a systematic discussion of these factors would be useful in establishing effective strategies for avoiding pitfalls in translation between English and Chinese.